Framing Nasionalisme dan Militerisme Amerika Serikat dalam Film Top Gun: Maverick: Analisis Framing Robert Entman - Pranoto, Muhammad Agum; Hariyani, Nunik; Hasan, Fikri (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the construction of United States nationalism in the film Top Gun: Maverick through Robert Entman's framing analysis. The study used a qualitative approach with a media textual analysis method. Data were obtained through observation and documentation of six purposively selected scenes, then analyzed using Entman's four framing devices: define problems, diagnose causes, make moral judgments, and treatment recommendations. Data validity was carried out through theoretical triangulation and expert judgment. The results show that the film frames global threats as legitimizing the use of United States military force, positioning technological superiority, professionalism, and soldier solidarity as solutions to these threats, and constructing a positive image of the military institution through representations of heroism and global leadership. These findings indicate that Top Gun: Maverick functions as a medium for legitimizing military policy through a framing strategy that integrates nationalist narratives with representations of military superiority. Academically, this research extends the application of Entman's framing model in the study of audiovisual media by showing how popular media construct ideological legitimacy for the use of military force through narrative and visual construction.